Euglycemic Diabetic Keto Acidosis in a Type 1 Diabetic Patient After Glucose Like Peptide-1 Administration: A Case Presentation - Cameron Widhalm OMS-IV; Victor Pulido DO (SAGE Publishing, 2023)
Type 1 diabetes mellitus (DM) occurs when insulin-producing beta cells are destroyed. Destruction of these cells and subsequent loss of insulin signaling can cause diabetic keto acidosis (DKA). This case describes a type 1 DM patient who presented to the emergency department (ED) with nausea and vomiting after glucose like peptide-1 (GLP-1) agonist administration. The patient was noted to have elevated anion gap and elevated beta-hydroxybutyrate with euglycemic blood glucose levels. The patient was confirmed to have a functioning insulin pump and then was sent home with nausea control. The patient was not able to consume food without vomiting and therefore did not administer any postprandial insulin. These symptoms were attributed to the GLP-1 agonist. It contributed to suppression of the patient's appetite while also inhibiting gluconeogenesis, and glycogenolysis resulting in small amounts of blood glucose entering the blood stream, negating the need for a bolus of insulin. The patient was admitted and given dextrose with an insulin drip until the anion gap was returned to normal. As GLP-1 agonists become more popular, this presentation may become more common. If not easily recognized this can lead to patient endangerment and unnecessary medical costs.